2013
DOI: 10.2967/jnumed.112.108688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of18F-FE-PEO in Rodents: An18F-Labeled Full Agonist for Opioid Receptor Imaging

Abstract: We have investigated the opioid receptor (OR) agonist (20R)-4,5-a-epoxy-6-(2-18 F-fluoroethoxy)-3-hydroxy-a,17-dimethyl-a-(2-phenyleth-1-yl)-6,14-ethenomorphinan-7-methanol ( 18 F-FE-PEO) as a candidate OR PET ligand. This tracer is attractive because it combines 18 F labeling, is suited to the slow kinetics of high-affinity ligands, and has agonist binding, which has been shown to be more sensitive to changes in OR occupation than is antagonist binding. Methods: Agonist potency and off-target binding were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Additionally, the time course of degradation of the radiotracers was determined by radio-HPLC analysis of the plasma samples from rats that were taken at different time points after tracer injection. 7 , 13 A nonlinear curve fit of the measured data was applied to the plasma activity curve to determine the metabolite-corrected plasma input function of the radiotracers ( Figure 5 B,F). No polar radiometabolites were detected in brain tissue up to a time point of 45 min p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the time course of degradation of the radiotracers was determined by radio-HPLC analysis of the plasma samples from rats that were taken at different time points after tracer injection. 7 , 13 A nonlinear curve fit of the measured data was applied to the plasma activity curve to determine the metabolite-corrected plasma input function of the radiotracers ( Figure 5 B,F). No polar radiometabolites were detected in brain tissue up to a time point of 45 min p.i.…”
Section: Resultsmentioning
confidence: 99%
“… 5 8 Our approach was motivated by ongoing discussions on the mechanism of displacement of the PET ligand from the OR receptor by endogeneous ligands and drug molecules. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“…This procedure gave [ 18 F]FE-PEO ( 17 ) in an isolated preparative yield of 35 ± 8% with a molar activity of 55–130 GBq/μmol. In 2013, a research group of the University of Cambridge [99] investigated [ 18 F]FE-PEO ( 17 ) as a candidate OR PET-ligand, obtained by an automated cGMP-compliant method the [ 18 F]FE-PEO at 28 ± 15% yield and 52–224 GBq/μmol molar activity. In 2014, Schoultz et al [63] reported the synthesis and biological evaluation of three structurally-related 6- O -(2-[ 18 F]fluoroethyl)-6- O -desmethy-orvinols, i.e.…”
Section: Radiotracers For the Pet Imaging Of Orsmentioning
confidence: 99%
“…Both radiotracers had a radiochemical purity > 95 % at the time of injection. [22] Animal experiments were conducted in accordance with national Norwegian regulations on the use of laboratory animals in research (FOR-2015-06-18-761), decision regarding the use of animals in procedures -FOTS ID 12701, establishment number 016: UiO-Institutt for medisinske basalfag (Domus Medica). Processed by the Norwegian Food Safety Authority (NFSA), 28.…”
mentioning
confidence: 99%
“…The Eppendorf vial was centrifuged for further 5 minutes. The supernatant was injected directly into the analytic HPLC [22] Other studies of GnRHÀ R antagonist have shown low brain penetration. [14] However, in our study both tracers enter the brain in a tenfold higher concentration as shown in Figure 1.…”
mentioning
confidence: 99%